The blueberry phyllosphere microbiota: tissue-specific core communities and their stability across cultivars and years - Matteo Giese; Erika Stefani; Simone Larger; Massimo Pindo; Brian Farneti; Matteo Ajelli; Monica Cattani; Manuel Delgado-Baquerizo; Lara Giongo; Claudia Coleine; Claudio Donati (BMC Plant Biology)
Summary Blueberries are critical for food production due to their widespread consumption and nutritional value. Beyond agriculture, wild Vaccinium species play essential ecological roles, including supporting pollinators and enhancing soil health. This dual importance underscores their relevance to both food security and ecosystem sustainability. The fruit-associated microbiome, both internal and surface-dwelling, includes a wide range of microorganisms. These microbial communities play a dual role: they influence fruit quality (e.g., taste, texture, shelf life) and are also involved in the degradation processes that occur during fruit senescence or postharvest storage.”. Despite their importance, the specific factors shaping the microbiomes of blueberry fruits, as well as their relationship with other above-ground parts of the plant and their stability over different years, remain poorly understood. We conducted a field experiment to characterize the taxonomic composition of fungal and bacterial communities colonizing the leaves and the surface and pulp of fruits on a collection of 10 different cultivars of blueberry over two years. Independently from the sampling time, pulp of the fruit, surface and leaves harbor specific and distinct microbiomes. A major factor determining the microbiome of blueberry fruits and leaves was plant cultivar, followed by tissue. We further identified the core microbiome for each plant tissue and demonstrated that core taxa account for the dominant fraction of the microbiota of each plant. As trade and production of blueberries is expanding, our results provide a foundation for advancing the development of targeted microbiome management strategies, with potential applications in enhancing plant health and productivity.